QUARTZ SOLUBILITY IN THE TWO-PHASE AND CRITICAL REGION OF THE NaCl-KCl-H2O SYSTEM: IMPLICATIONS FOR SUBMARINE HYDROTHERMAL VENT SYSTEMS AT 9°50′N EAST PACIFIC RISE - Foustoukos D.I.; Seyfried W.E. (My University, 2007)
Experiments were performed to investigate quartz solubility in Cl-bearing aqueous solutions at temperature (365-430 °C) and pressure conditions (219-381 bars) near and within the two-phase region of the NaCl-KCl-H2O system. Dissolved SiO2 concentrations increased with pressure along a given isotherm, although the magnitude of this decreased with increasing proximity to the two-phase boundary. Upon intersection of the two-phase boundary, however, significant concentrations of dissolved SiO2 characterized vapor-rich fluids at both subcritical and supercritical conditions. For these fluids, dissolved silica concentrations ranged from 2.81 to 14.6 mmolal, increasing with dissolved chloride concentration. The experimental data permit regression of a density-based relationship, taking account of non-ideal activity-concentration effects, which can be used to better constrain temperatures and pressures from dissolved SiO2 and chloride in high temperature vent fluids at mid-ocean ridges. Accordingly, pressure and temperature conditions in subseafloor hydrothermal reaction zones at 9°50′N East Pacific Rise (EPR) were estimated applying data from this experimental study to interval (1991-2002) and new field data (2004). Results indicate reaction zone at conditions ranging from 420 to 430 °C at 600 to 1500 m below seafloor. Thus, conditions predicted for 9°50′N East Pacific Rise (EPR) vent fluids suggest that supercritical phase separation might be more common than previously thought. © 2006 Elsevier Inc. All rights reserved.